Kratkii katalog arabskikh rukopisei i dokumentov Rossiiskogo gosudarstvennogo arkhiva drevnikh aktov = Handlist of Arabic manuscripts and documents in Russian state archives of ancient acts - Morozov, D. A. (Moskva)
109 s.